(untitled) (Dhaka University Journal of Science, 2017)
Logistic dynamics are frequently encountered in real life problems, especially in population dynamics. Data showing an appearance to follow logistic model may be interpolated by standards methods in numerical analysis. In this paper we discuss a method to fit a curve to such data using the intrinsic analytic properties of the data in terms of least square method and graphic tools in the environment of Mathematica. Dhaka Univ. J. Sci. 65(2): 103-105, 2017 (July)